ANALISIS PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BEI PERIODE 2014-2017 - Natasya Kurniadi Lukiman; Yudith Dyah Hapsari (Prosiding Working Papers Series In Management, 2018)
Maximizing the wealth of investors is the company’s main goal. This study will examine the effect of capital structure as measured by DER and profitability as measured by ROA to firm value as measured by PBV. Sample of this study are the consumer goods companies listed on IDX for period 2014-2017. Total sample used is 24 companies. The result of this study indicates that the capital structure (DER) and profitability (ROA) have a significant positive effect on firm value (PBV).Keywords: firm value, PBV, capital structure, DER, profitability, ROA.